The Outsiders - Paver, Michelle (Gods and warriors ; 1, 2014)
'If an Outsider wields the blade, the House of Koronos burns . . . ' Hylas is only a boy but he knows three things- The Gods exist. Magic is real. Somebody wants him dead. Hunted and alone, Hylas is desperate to find his missing sister. His quest takes him across the hostile mountains and treacherous seas of Ancient Greece. His only friend is a girl on the run. His only guide is a wild dolphin. And his murderous enemies are closing in . . . The first book in a spellbinding new series from Michelle Paver, bestselling author of Wolf Brother. 'Electrifying' Independent on Sundaywww.godsandwarriors.co.uk